Does the healthy immigrant effect apply to mental health? Examining the effects of immigrant generation and racial and ethnic background among Australian adults - Rennie Lee (Elsevier, 2019)
The healthy immigrant effect (HIE) refers to the phenomena in which immigrants show greater health outcomes than the native-born population. However, it is unclear what is the extent to which HIE applies to various outcomes and populations. Much of the work on HIE has revolved around physical health outcomes; mental health, however, has not garnered the same level of attention with regard to HIE. It is also uncertain whether immigrants' health advantage persists beyond one generation. This study assesses the mental health of the first, second, and third and higher generations (70,517 person-year observations) for individuals from various racial and ethnic backgrounds in Australia using Waves 1−16 of the Household Income and Labour Dynamics in Australia survey. The dependent variable is mental health score and key independent variables include generation and racial and ethnic background. I control for age, educational attainment, labor force status, marital status, remoteness, household income, language, neighborhood disadvantage, citizenship, weight, and gender. Using linear regression with random effects, this study finds that mental health varies by generation; the third and higher generation show the greatest mental health score, followed by the first generation and the second generation, net of controls. Mental health score also varies by racial and ethnic background. Except for English-speaking groups, native-born Australians show a clear advantage over Europeans, North Africans/Middle Easterners, and Asians. Racial and ethnic disparities differ by generation and are strongest among the first generation. My findings extend HIE, which typically emphasize immigrants' superior health outcomes over the native-born population but do not focus on racial and ethnic disparities among immigrants. My results suggest that immigrant groups vary widely in their mental health outcomes but these lessen over time. Overall, the findings suggest the limited applicability of HIE for a broad range of health outcomes and populations. Keywords: Healthy immigrant effect, Australia, mental health, children of immigrants, race and ethnicity